2017
DOI: 10.1515/afe-2017-0089
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Type of Welding Sequence During Hardfacing Chromium Cast Iron for Erosion Resistance

Abstract: The paper presents the capabilities of welding techniques to creating properties of wear resistant high chromium cast iron alloy. The use of the right kind of welding sequence allows you to change the structure and properties of the obtained welds. Tests were conducted for one type of additive material in the form of self shielded core wire. In order to determine the effect of the type of welding sequence on the properties of welds performed welding using string bead and weave bead. The resulting weld was test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 14 publications
(12 reference statements)
0
5
0
Order By: Relevance
“…Macrostructure analysis, hardness test, and a tribological test by the method "ball on flat" was performed on the hardfacing weld. [10,11,12,14].…”
Section: Experiments Methodologymentioning
confidence: 99%
“…Macrostructure analysis, hardness test, and a tribological test by the method "ball on flat" was performed on the hardfacing weld. [10,11,12,14].…”
Section: Experiments Methodologymentioning
confidence: 99%
“…An example of such an element is titanium, which when added in the laser alloying of a ductile cast iron surface causes the formation of high-hardness titanium carbides in the structure of the surface layer, which has a beneficial effect on the wear resistance of the surface. Research in the field of laser alloying of ductile cast irons with titanium has shown that with the appropriate selection of process parameters, it is possible to produce homogeneous surface layers and control their structure and properties, including the fraction, size and morphology of titanium carbides [20][21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…Titanium, besides high affinity to carbon, also has a high affinity to nitrogen and can form titanium nitrides and carbonitrides, which, like carbides, exhibit high hardness and can reinforce the composite structure for high wear resistance [25,26]. Many studies on titanium surface nitriding have been conducted, and the results are available in the literature [27,28], while only a few studies have been conducted on ductile cast iron surface alloying with titanium and nitrogen [29].…”
Section: Introductionmentioning
confidence: 99%
“…Most of the hardfacing techniques are based on the welding processes [5] and high carbon and chromium materials. Thank to their good wear resistance and low cost, iron-based hardfacing alloys are frequently employed in industry to extend the service life of components subjected to abrasive, erosive or metal to metal wear conditions, such as rocking pulverizing, crushing to applications and transport systems [6][7][8][9][10][11][12][13]. One of the interesting hardfacing techniques is self shielding arc welding with cored wire.…”
Section: Introductionmentioning
confidence: 99%